Facial profile attractiveness in patients treated with Bionator and Herbst - Kurimori, Érika Tiemi (2024)
Objective: The aim of this study was to assess the perception of laypersons, dentists, and orthodontists regarding the attractiveness of the facial profile of patients treated with Herbst after a 14-year follow-up of orthopedic mandibular advancement. Secondly, to compare the attractiveness of the facial profile of patients treated with Bionator or Herbst after orthopedic treatment. Methods: The initial sample comprised 13 patients treated with Herbst. Pre-treatment (T0), post-orthopedic treatment (T1), post-fixed appliance (T2), and long-term (T3) cephalometric radiographs were obtained. Additionally, pre- and post-orthopedic treatment cephalometric radiographs were collected from 32 patients treated with Bionator (Group B, n=16) or Herbst (Group H, n=16). Images of the facial profile silhouette were obtained through cephalometric tracing and randomly organized for evaluation. Three groups of examiners (35 laypersons, 35 general dentists, and 35 orthodontists) rated the attractiveness of the facial profile using a numeric visual analog scale ranging from 1 (least attractive) to 10 (most attractive). Comparisons between groups regarding initial age, mean treatment time, and appliance type (B or H) were performed using t-tests. Sex distribution was compared between patient and evaluator groups using the chi-square test. Inter-group comparisons of examiners were conducted using the Kruskal-Wallis test. Friedman and Wilcoxon tests were used to assess differences between time points. Results: According to the perception of the three groups of examiners, there was a significantimprovement in the attractiveness of the facial profile after therapy with Bionator or Herbst. In the long-term evaluation, there was a reduction in attractiveness following Herbst use. Dentists were significantly more critical than laypersons and orthodontists. Only at pre-treatment was there a significant difference between male and female examiners (p=0.015). Conclusions: Both Bionator and Herbst appliances had a positive impact on the facial profile. After a 14-year follow-up of orthopedic treatment with Herbst, the perception of facial profile attractiveness remained more positive than at pre-treatment. Dentists were found to be more critical than laypersons and orthodontists.